2013
DOI: 10.1016/j.heares.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and therapeutic functions of drug combinations against noise-induced hearing loss

Abstract: Noise is the most common occupational and environmental hazard. Noise-induced hearing loss (NIHL) is the second most common form of sensorineural hearing deficit, after age-related hearing loss (presbycusis). Although promising approaches have been identified for reducing NIHL, currently there are no effective medications to prevent NIHL. Development of an efficacious treatment has been hampered by the complex array of cellular and molecular pathways involved in NIHL. We turned this difficulty into an advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 74 publications
(92 reference statements)
0
21
0
Order By: Relevance
“…A recent study demonstrated that calciumblocking anticonvulstants can be protective against noiseinduced hearing loss. 24 Together these results provide strong support for use of CCBs as otoprotective agents against ototoxicity. In this study, diltiazem was used because it is an antagonist of L-type calcium channels, which provided a targeted approach to prevent calcium-mediated apoptosis of cisplatin ototoxicity.…”
Section: Discussionmentioning
confidence: 63%
“…A recent study demonstrated that calciumblocking anticonvulstants can be protective against noiseinduced hearing loss. 24 Together these results provide strong support for use of CCBs as otoprotective agents against ototoxicity. In this study, diltiazem was used because it is an antagonist of L-type calcium channels, which provided a targeted approach to prevent calcium-mediated apoptosis of cisplatin ototoxicity.…”
Section: Discussionmentioning
confidence: 63%
“…Antioxidant compounds [20][21][22][23][24][25][26][27][28], glutamate antagonists [56], calcium channel blockers [57], JNK inhibitors [58,59] and glucocorticoid compounds [57,60] have all demonstrated protective or therapeutic effects against NIHL, and do not represent an exhaustive list of the classes of compounds that have been tested. Src inhibitors have clearly demonstrated a potential protective effect when the compound is delivered directly into the cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, only the L-type CCBs appeared to reduce the auditory loss [76]. Our recent studies found that trimethadione and ethosuximide were protective of auditory hair cells and spiral ganglion neurons (SGNs) [59,5]. However, similar to in vitro studies, it was unclear whether this neuroprotection in vivo was due to blocking of T-type calcium channels or regulating other signaling pathways.…”
Section: Neuroprotection Evidence From In Vitro and In Vivo Modelsmentioning
confidence: 99%
“…As we will now discuss, blockers for T-type calcium channels have been developed to treat various diseases. These blockers show neuroprotective effects both in vitro and in vivo [59,80,42,5]. However, molecular mechanisms underlying their neuroprotective effects are still unclear.…”
Section: Introductionmentioning
confidence: 99%